2017
DOI: 10.1103/physrevlett.119.256404
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality-Driven Metal-Insulator Transition in Spin-Orbit-Coupled SrIrO3

Abstract: Upon reduction of the film thickness we observe a metal-insulator transition in epitaxially stabilized, spin-orbit-coupled SrIrO_{3} ultrathin films. By comparison of the experimental electronic dispersions with density functional theory at various levels of complexity we identify the leading microscopic mechanisms, i.e., a dimensionality-induced readjustment of octahedral rotations, magnetism, and electronic correlations. The astonishing resemblance of the band structure in the two-dimensional limit to that o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 50 publications
6
64
1
Order By: Relevance
“…Nevertheless, the MOKE measurements confirm the large lattice symmetry dependence (θ k = 0.15 ± 0.01 in the 25-uc SrIrO 3 sample, and 0.013 ± 0.01 in the 8-uc SrIrO 3 sample) and the anisotropic ST ratio (θ k = 0.15 ± 0.01 with j c jja axis, and 0.05 ± 0.005 with j c jjb axis in the 25-uc SrIrO 3 sample), which are qualitatively To analyze the effect of lattice symmetry on spin-Hall effect in detail, we studied the dependence of the ST ratio on varying thicknesses of SrIrO 3 films. From synchrotron X-ray measurements, we robustly established the previously discussed suppression of IrO 6 octahedral tilt for ultrathin SrIrO 3 films, which modifies the symmetry of SrIrO 3 from orthorhombic to tetragonal (see SI Appendix for details) (41)(42)(43). As shown in Fig.…”
Section: Significancesupporting
confidence: 67%
“…Nevertheless, the MOKE measurements confirm the large lattice symmetry dependence (θ k = 0.15 ± 0.01 in the 25-uc SrIrO 3 sample, and 0.013 ± 0.01 in the 8-uc SrIrO 3 sample) and the anisotropic ST ratio (θ k = 0.15 ± 0.01 with j c jja axis, and 0.05 ± 0.005 with j c jjb axis in the 25-uc SrIrO 3 sample), which are qualitatively To analyze the effect of lattice symmetry on spin-Hall effect in detail, we studied the dependence of the ST ratio on varying thicknesses of SrIrO 3 films. From synchrotron X-ray measurements, we robustly established the previously discussed suppression of IrO 6 octahedral tilt for ultrathin SrIrO 3 films, which modifies the symmetry of SrIrO 3 from orthorhombic to tetragonal (see SI Appendix for details) (41)(42)(43). As shown in Fig.…”
Section: Significancesupporting
confidence: 67%
“…results in a localization of the carriers, and triggers a transition from a semimetallic to an AFM insulating state. Even for a single layer of SrIrO 3 on SrTiO 3 the nonmagnetic case is found to be metallic, and AFM ordering is required for the opening of a gap [28]. The electronic structure of the 4 u.c.…”
Section: Spin-orbit Semimetal Sriro 3 In the Two-dimensional Limitmentioning
confidence: 99%
“…Here, both electron-electron interactions and weak antilocalization contribute to the negative magnetoconductance. Structural studies have shown that octahedral coupling at the SrTiO 3 =SrIrO 3 interface suppresses the bulk octahedral rotations in the SrIrO 3 film for t < 4 u.c., enhancing magnetic interactions [28]. Within this view, the increase of χ as the film thickness is reduced can be understood as an increased fractional contribution from the less distorted magnetic interfacial region.…”
Section: Spin-orbit Semimetal Sriro 3 In the Two-dimensional Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In the case of sample S1 ( Fig.1 B top weak [19]. SIO is a correlated paramagnetic semimetal; SIO thin films do not show long-range magnetic order down to low temperatures [20,21]. Previous reports demonstrate a small magnetic moment of 0.05 B/Ir at the interface coupled antiparallel to the Mn moment [13,14].…”
Section: A2 Atomic Structure At Interfaces (Stem)mentioning
confidence: 84%